Activated treatment of magnesite for preparing size-controlled Mg2B2O5 whiskers and their microwave dielectric properties. Issue 21 (1st November 2021) - Liu, Zhaoyang; Yu, Jingkun; Wang, Xiangnan; Zhang, Ling; Wang, Jiakang; Jin, Endong; Jia, Danbin; Wen, Tianpeng; Yan, Zhengguo; Yuan, Lei; Ma, Beiyue
Abstract: In this study, magnesite was activated through hydration and balling treatment, and the received MgO with high activity and H3 BO3 were used as raw materials for synthesizing Mg2 B2 O5 whiskers with the aid of KCl salt. Attention was paid to the effects of B/Mg ratio and reaction temperature on the phase transformation and morphology evolution of the produced whiskers, and their growth mechanism was proposed as well. The Mg2 B2 O5 ceramics were prepared based on the whiskers with different diameters via traditional pressing-sintering. Their physical properties, such as bulk density, apparent porosity and Vickers hardness (Hv), were studied. Particular emphasis was placed on the relationship between microstructure and microwave dielectric properties ( ε, Q  ×  f, and τ f ) of the Mg2 B2 O5 ceramics. According to the results, the higher B/Mg ratio and the lower reaction temperature were more suitable for the growth of Mg2 B2 O5 whiskers with high aspect ratio conforming to the liquid-solid (LS) mechanism. In particular, the Mg2 B2 O5 ceramics based on the whiskers with average diameter (AD) = 198 nm and sintered at 1250 °C exhibited good microwave dielectric properties ( ε  = 6.18, Q  ×  f  = 18, 597 GHz, and τ f  = −82 ppm/°C). This new design principle provides a guidance for fabricating high value-added magnesia-based ceramics from magnesite.